CYBERBULLYING’S FORMS AND IMPLICATIONS AMONG STUDENTS WITH PESANTREN BACKGROUND AND ACTIVE SOCIAL MEDIA USERS - Erni Dewi Riyanti; Galih Cipto Raharjo; Fadhillah Zahra Widafina (Kopertais Wilayah X Jawa Tengah, 2022)
As internet users in Indonesia increased by 11% from the previous year, Indonesians are getting more immersive with digital environment. In addition, the pandemic may be one of the drivers of the increase. The trend of using social media has a significant impact on people's social life, including the occurrence of bullying through online media, known as cyberbullying. The study aims to identify forms and impacts of cyberbullying among students of Faculty of Islamic Studies, Universitas Islam Indonesia with pesantren background and active social media users. With the descriptive qualitative method, the researchers applied purposive sampling in determining the respondents. The results of this study indicate that 84.6% of respondents know the definition of cyberbullying. 61.5% of respondents stated that they experienced at least 2 of 7 types of cyberbullying. The interview shows 3 forms of cyberbullying, such as, online harassments, flaming, and exclusion. The informants' reactions to cyberbullying are feeling annoyed, angry, hurt, disappointed, afraid, shock, overthinking, insecure, anxious, embarrassed, sad, concerned, retaliation to the perpetrators, and suicidal attempt. The informants' coping mechanisms are meeting a professional, remaining silent, suppressing their feelings, holding back their anger, blocking any communication access to the bully, and conducting activities to distract them from the occurred cyberbullying (e.g., playing games, journaling, relaxing, and sleeping). The interview also indicates negative and positive consequences of cyberbullying. Finally, the informants believes that social media ethics promoted via digital literacy campaign to young adults will be a solution which will significantly contribute to preventing cyberbullying.